The HCV Synthesis Project: scope, methodology, and preliminary results. - Stern, Rebecca K; Hagan, Holly; Lelutiu-Weinberger, Corina; Jarlais, Don Des; Scheinmann, Roberta; Strauss, Shiela; Pouget, Enrique R; Flom, Peter (BMC medical research methodology, 2008)
The hepatitis C virus (HCV) is hyper-endemic in injecting drug users. There is also excess HCV among non-injection drug users who smoke, snort, or sniff heroin, cocaine, crack, or methamphetamine.
Keywords: Epidemiologic Methods; Female; Hepatitis C; Humans; Information Storage and Retrieval; Male; Pilot Projects; Research Design; Risk Factors; Substance Abuse, Intravenous; Substance-Related Disorders